Antioxidant Activity in Gilthead Seabream (Sparus aurata L.) Fed with Diet Supplemented with Moringa - Antonia M. Jiménez-Monreal; Francisco A. Guardiola; M. Ángeles Esteban; M. Antonia Murcia Tomás; Magdalena Martínez-Tomé (MDPI AG, 2021)
Gilthead seabream is bred mainly in fish farms in the Mediterranean Sea. One important factor responsible for the deterioration of fish quality is lipid oxidation. Moringa oleifera leaves have been described as having high antioxidant content. This work investigates the effect of dietary supplementation with Moringa leaves on the antioxidant activity of seabream. Gilthead seabream specimens were divided into four groups, the control group (fed a commercial diet) and three other groups fed diets enriched with Moringa (5%, 10% and 15%). The antioxidant capacity was measured by assays of free radical scavenging (OH·, H2O2, lipoperoxyl and ABTS), Rancimat test and linoleic acid system in muscle and skin of gilthead seabream, commercial diet, enriched diet and Moringa. Finally, the polyphenol content of Moringa and the fatty acid composition of seabream fed diets with and without Moringa were determined. Results showed an increase in antioxidant activity in gilthead seabream fed with diets enriched with a higher percentage of Moringa; therefore, Moringa could be considered a functional ingredient in diets for fish bred in fish farms and. The antioxidant potential of Moringa leaves could be mainly attributed to the presence of polyphenolic compounds.